IMAN DI TENGAH KETAKUTAN : Berdasarkan Analisa Eksistensial atas Angin ribut diredahkan (Mrk. 4: 35-41) - Laurensius tonny Kuntag; Antonius Tukiran (Pineleng Theological Review, 2026)
This paper analyzes the passage of Mark 4:35–41 (Jesus Calming the Storm) using narrative hermeneutics, socio-historical analysis, and Wirkungsgeschichte(reception history) to uncover the dynamics of faith and fear within the human experience. This pericope is understood not merely as a report of a nature miracle, but as a theological narrative intentionally constructed by Mark to shape the faith of the disciples and the reader’s community amidst crisis. The textual-narrative analysis reveals a structural movement from stillness to chaos and back to silence, mirroring the existential dynamics of humans when faith is tested by tangible threats. The disciples' fear is characterized as not only emotional but primarily relational and existential—a crisis of trust regarding the perceived indifference of a "silent" God. Jesus’ sleep during the storm is interpreted as Mark’s theological strategy to challenge instrumental faith and direct the reader toward a mature faith. In its socio-historical context, the passage reflects the experiences of the Markan community, which faced political pressure and persecution in the first century. Through the lens of Wirkungsgeschichte, this study demonstrates how the text continues to function within Church tradition as a source of spiritual formation, consolation, and existential courage. The primary conclusion asserts that Christian faith does not eliminate fear but transforms it through the presence of Christ in the midst of life’s "storms."